FAKTOR EKSPLOITASI JENIS MERANTI DI JAMBI, KALIMANTAN TENGAH DAN KALIMANTAN TIMUR - Sampe Radja Simarmata; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1985)
The study was carried out in three locations  in Jambi, Central Kalimantan and East Kalimantan. The number of forest companies observed  in each location  varies  from 2 to 4 which  were randomly  selected.The study  concludes that  :The  logging waste  ranges from 16,3 %  to 24,6 % of the clear bole volume. The average logging waste is 22,2  % consists of 12,2 %  trimming waste and stumps, and 9 % defects.The  exploitation  factor  ranges from 75,4 % to 83,7 % and  the average is 0,80.  This value  was previously  used for the observed  locations.Diameter class has a highly significant effect (P<0,01) on exploitation  factor.  The  exploitation  factor proportionally increases  with  the log diameters.